What Things Cost : an anthology for the people - Jones, Ashley M., 1990-; Howell, Rebecca Gayle (Book collections on Project MUSE., 2023)
"By 1968, most Americans felt that the War on Poverty had been lost, cast out to the shadows of the Vietnam War. That same year, the Poor People's Campaign marched on Washington in the wake of Martin Luther King's assassination, motivated by King's desire for economic justice. The campaign was a multiracial effort that aimed to alleviate poverty for African Americans, white Americans, Asian Americans, Hispanic Americans, and Indigenous people. In 2017, the Poor People's Campaign: A National Call for a Moral Revival was launched with the goal to bring King's "revolution of values" to fruition. In What Things Cost, Ashley M. Jones and Rebecca Gayle Howell present an anthology of contemporary poems that speak to the current state of the labor movement. Designed to be a fundraiser for The Poor People's Campaign, What Things Cost employs the power of verse and storytelling to illuminate the painful difficulties of building a healthy life in modern America. Like the campaign itself, the poems bridge lived experiences of struggle across racial and historical divides. The effect is a folkloric journey through America's contemporary landscape. The common theme of work threads through this rich literary quilt, revising outdated American Dream mythology. Jones and Howell blanket tales of hardship, gratitude, guilt, grievance, and solidarity within this volume, with the goal of creating an economically just country"--